Eqüidade e reforma setorial na América Latina: um debate necessário Equity and health sector reform in Latin America: a necessary debate - Celia Almeida (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
Reforma e eqüidade são termos que têm freqüentado os discursos políticos, documentos técnicos e discussões conceituais nas últimas décadas em distintas propostas com diferentes referenciais ideológicos. Entender a importância e centralidade desses temas no debate contemporâneo na América Latina pressupõe aprofundar a reflexão sobre a política de saúde no âmbito das políticas sociais, qualificar de que reformas estamos falando e o lugar que a eqüidade ocupa nessa discussão. Na primeira parte deste ensaio, discutem-se os conceitos de reforma e eqüidade; a seguir, faz-se um repasse sobre política de saúde como política social; e por fim, são discutidos os elementos centrais da agenda de reforma de sistemas de saúde na região. Conclui-se que a situação é dramática, as reformas recentes exacerbaram as desigualdades e criaram novos problemas, ao substituir valores de solidariedade e igualdade de oportunidade pelos de um "individualismo utilitarista radical"; e o princípio de "necessidades de saúde" pelo de "risco", monetarizado e definido segundo a posição social e econômica do indivíduo. Faz-se necessário retomar a discussão das políticas sociais e de saúde como a matriz de princípios que justificam o ordenamento de quaisquer outras políticas. Reform and equity are terms that have frequented political discourse, technical documents, and conceptual discussions in recent decades in different proposals with different ideological references. To understand the importance and centrality of these themes in the contemporary debate in Latin America implies a more in-depth reflection on health policy in the sphere of social policies and to define which reforms were are discussing and the place equity occupies in this discussion. The first part of this essay discusses the concepts of reform and equity, followed by a review of health policy as a social policy. The article ends by discussing the central elements on the health systems reform agenda in Latin America. The conclusion is that the situation is dramatic and that recent reforms have exacerbated inequalities and created new problems by replacing the values of solidarity and equal opportunity with those of "radical utilitarian individualism"; meanwhile, the principle of "health needs" has been replaced by that of "risk", "monetarized" and defined according to the individual's social and economic position. It becomes necessary to resume the discussion of social and health policies as the matrix of principles justifying the order ascribed to any other policies.